Effects of Sowing Dates and Nitrogen Application on Phosphorus and Potassium Contents in Parsley - YOLDAS, FUNDA; CEYLAN, SAFAK; MORDOGAN, NILGUN; CAKICI, HAKAN (Asian Journal of Chemistry, 2010)
The effects of increased N rates (0, 100, 200 and 300 kg N ha-1) on yield, plant length, number of stalk, phosphorus and potassium content in parsley leaf and stalk during seven harvesting at two sowing time were investigated.